Niveles de hemoglobina y hematocrito con el índice de masa corporal, edad y sexo y determinación del riesgo de anemia en pobladores adultos del sector de Buenos Aires Sur, del distrito de Víctor Larco Herrera, Mayo 2017 - Barrientos Córdova, Jonathan Jair (2017)
The present study aimed to determine the level of hemoglobin and hematocrit in adult patients treated at the health post of Buenos Aires Sur in the district of Víctor Larco Herrera, May 2017, with prior informed consent. Sixty blood samples obtained from the toe of the finger were used. The biochemical determinations of hemoglobin were based on the spectrophotometric method (ferrous iron is oxidized to ferric iron and subsequent quantification of cyanometahemoglobin formed) and hematocrit, using the microhematocrit method (separation of plasma erythrocytes by the action of centrifugal force and measurement of volume of them). With the data obtained it was observed that 83.6% of the total of patients were women and the rest, males. 83.6% of the patients had normal hemoglobin values and 11.5% of the total had decreased values. Thus, 90.2% of the total number of patients had normal hematocrit values and 1.6% of the total number of patients had decreased hematocrit values, and 3.3% were found to be overweight. The chi-square test was used to determine the relationship between hemoglobin and hematocrit levels with BMI, age and sex, revealing that there is no significant relationship between these variables (p> 0.05). Concluding that the levels of hemoglobin and hematocrit are not influenced by age, sex and BMI